Hybrid vigour on 'Sunki' mandarin - Filho, Walter dos Santos Soares; Moreira, Célio dos Santos; Cunha, Mario Augusto Pinto da; Sobrinho, Almir Pinto da Cunha; Passos, Orlando Sampaio; Morais, Lucymeire Souza (Pesquisa Agropecuaria Brasileira, 1999)
Controlled crosses of 'Sunki' with Poncirus trifoliata and its hybrids were performed in order to estimate the zygotic seedlings frequency, by comparing its vigour with the ones from nucellar origin. A relatively high fruit set rate of 40% was achieved, which indicates a good compatibility within the parental crosses. The observed frequency of zygotic seedlings was 48% and certainly this was underestimated due to the presence of Poncirus hybrids in the pollinations. Epicotyl length and the true leaf number character estimates showed that 91% of the identified hybrids may be similar or even superior to the nucellar ones in relation to plant vigour.
Keywords: Verificar porque não conseguiu capturar os termos em ingles